Proyecto de educación para la sexualidad y construcción de ciudadanía: avances y retos de su implementación - Sánchez-Chávez, Andrea del Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The project of education for sexuality and construction of citizenship PESCC has represented a challenge for the Colombian state since its promulgation. The purpose of this document is to know the status of the proposal, achievements and pending challenges, through the literature review of different research projects developed in the country since its implementation. There are strengths in terms of relevance to the proposed objectives and methodologies, ownership and willingness to dialogue, transformation and mobilization social, but it is evident that the influence of political and sociocultural factors, as well as, the lack of sectorial integration and qualified counselors in the subject have impeded the progress of it.